Позиционные наблюдения VI спутника Юпитера в ГАО АН УССР в 1987–1988 гг. - Ижакевич, Е.М.; Калтыгина, С.В.; Майор, С.П.; Шатохина, С.В. (Кинематика и физика небесных тел, 1991)
Приводятся результата 12 наблюдений Гималаи, выполненных в Голосеево и на горе Майдакак в 1987—1988 гг., и их сравнение с эфемеридой. Twelve photographic astro-metric observations of Himalia made at Goloseevo and Mt Majdanak from September 1987 to January 1988 are reported. Residuals derived from comparison between observed and computed positions of the satellite are also given.